SOCIAL SERVICES Berbasis Desa dalam Mendukung Inklusi Penyandang Disabilitas: STUDI KASUS PADA DESA TAMBAKBAYA KECAMATAN GARAWANGI KABUPATEN KUNINGAN - Cynthia, Astrid; Andayani, Rini Hartini Rinda (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
ABSTRACT Village-level social services play a strategic role in safeguarding the rights and well-being of vulnerable groups, including persons with disabilities. However, the practice of social services at the village level still faces various constraints, including institutional, accessibility, and service integration challenges. This study aims to analyse how village-based social services are developed and implemented to support the inclusion of persons with disabilities through a case study of Tambakbaya Village, Garawangi District, Kuningan Regency. The study adopts an action research approach involving village government, communities, social service institutions, and relevant stakeholders, which facilitated the enactment of Kuningan Regent Regulation Number 400.9/KPTS.955-Dinsos/2025 on Designating Tambakbaya Village, Garawangi District, as a Model for Replication of a Village-Friendly Mental Disability Model. Furthermore, the study advocates for implementing this regulation by strengthening village social services through the establishment of the Social Welfare Centre (Puskesos), Community-Based Rehabilitation (CBR), adaptation of health service mechanisms, and the integration of economic empowerment via the Sheltered Workshop for Care (SWP). While challenges remain in terms of resource limitations, the capacity of local cadres, and the development of social empowerment outcomes, the findings affirm that integrated and collaborative village-based social services constitute the fundamental foundation for sustainable, inclusive village development. KEYWORDS social services; inclusive village; disability;, action research; social empowerment. ABSTRAK Social services (social services) di tingkat desa memiliki peran strategis dalam menjamin pemenuhan hak dan kesejahteraan kelompok rentan, termasuk penyandang disabilitas. Namun, praktik social services di desa masih menghadapi berbagai keterbatasan, baik dari sisi kelembagaan, aksesibilitas, maupun integrasi layanan. Penelitian ini bertujuan untuk menganalisis bagaimana social services berbasis desa dikembangkan dan diimplementasikan dalam mendukung inklusi penyandang disabilitas melalui studi kasus Desa Tambakbaya, Kecamatan Garawangi, Kabupaten Kuningan. Penelitian ini menggunakan pendekatan action research dengan melibatkan pemerintah desa, masyarakat, lembaga layanan sosial, dan pemangku kepentingan terkait, yang mendorong ditetapkannya Peraturan Bupati Kuningan Nomor 400.9/KPTS.955-Dinsos/2025 tentang Penetapan Desa Tambakbaya Kecamatan Garawangi Sebagai Percontohan/Replikasi Model Desa Ramah Penyandang Disabilitas Mental. Selain itu, penelitian ini juga mendorong implementasi peraturan tersebut dengan penguatan social services desa melalui pembentukan Pusat Kesejahteraan Sosial (Puskesos), Rehabilitasi Berbasis Masyarakat (RBM), adaptasi mekanisme layanan kesehatan, serta integrasi pemberdayaan ekonomi melalui Sheltered Workshop Peduli (SWP). Sekalipun masih terdapat tantangan yang dihadapi pada keterbatasan sumber daya, kapasitas kader lokal serta pengembangan hasil pemberdayaan sosial, namun temuan ini menegaskan bahwa social services berbasis desa yang terintegrasi dan kolaboratif merupakan fondasi utama dalam pembangunan desa inklusif yang berkelanjutan. KATA KUNCI: social services; desa inklusi; disabilitas; action research; pemberdayaan sosial.